Impact of pore structure and fractal characteristics on the sealing capacity of Ordovician carbonate cap rock in the Tarim Basin, China. (April 2019) - Wu, Jun; Fan, Tailiang; Gomez-Rivas, Enrique; Gao, Zhiqian; Yao, Shuqing; Li, Wenhuan; Zhang, Chenjia; Sun, Qingqing; Gu, Yu; Xiang, Man
Abstract: Evaluating the heterogeneity and sealing capacity of carbonate cap rocks is of great significance for hydrocarbon production. However, the main controls on pore size distribution in carbonate cap rocks are not well constrained. In this contribution we analyze drill core samples of carbonate cap rocks from the Ordovician Yingshan Formation (Tarim Basin) to study their pore properties and investigate the controls of pore-throat structure and fractal dimension on the sealing capacity of the cap rock. Results from petrography and a combination of mercury injection capillary pressure and nitrogen gas adsorption tests reveal that there are four lithological cap rock types, with micrite being the most prevalent one, followed by calcarenite. Six types of pore-throat structures and fractal dimensions (from D1 to D6 ) are classified based on the pore size distributions, including macropore-I, macropore-II, mesopore-I, mesopore-II, transitional pore-I and transitional pore-II. The fractal dimensions show that there is a decreasing trend from D1 to D6 with decreasing pore-size diameter, suggesting that the macropore and mesopore types present more complex pore-throat structures than the transitional type. The total fractal dimension (Dtotal ) indicates that the pore throat structures are complex and heterogeneous. The sealing heights of the gas column have a positive correlation with cement content in calcarenite and a negative correlation with microfracture density. Mesopore-II and transitional pore types make a significant contribution to enhancing the breakthrough pressure. The fractal variations mainly result from macropores and mesopores, while transitional pores and micropores weaken the impact of the whole pore system on the Dtotal value. The heterogeneity and anisotropy of macropores is the main control on the sealing capacity of the cap rock. The increasing of D1 considerably contributes to the pore shape heterogeneity and enhances the capillary resistance force to hydrocarbon migration. Therefore, the fractal dimension is an effective approach for investigating the pore throat structure and sealing capacity of carbonate cap rocks. Highlights: Pore size distributions of carbonate cap rock were quantitatively investigated using MICP and N2 GA. Controls of microfractures and cementation on sealing capacity were analyzed. Fractal dimensions were adopted to characterize the heterogeneity of cap rock. Correlation between fractal dimension and sealing capacity was discussed.